China’s disaster diplomacy in Southeast Asia - Gong, Lina (2022)
Disaster management provides an avenue for extraregional partners to engage with the Association of Southeast Asian Nations (ASEAN) and its member states, as Southeast Asia is highly exposed to natural hazards. is article examines how China has managed its bilateral and multilateral relations with the region through engagement on disaster management and explores the factors that have shaped the e ectiveness of its diplomatic o ense in this area. e existing studies point to three issues that can influence the success of disaster diplomacy, which include mobilization, communication, and acceptance. This article argues that China’s evolving aid system has led to mixed results of its disaster diplomacy in Southeast Asia. State-centricity enables rapid mobilization and deployment of resources and personnel through official channels for overseas disaster relief missions. Nevertheless, capacity limitations restrict the scope and modality of China’s involvement, and institutional constraints a ect its communication with the recipient country/organization. Moreover, state-centricity makes China’s overseas disaster-related activities susceptible to politics, which adversely impact acceptance by the recipients. e article selects four empirical cases to demonstrate how state-centricity has in uenced the outcome of China’s disaster diplomacy in Southeast Asia, which include ASEAN, the Philippines, Myanmar, and Indonesia.